How Financial Literacy Moderate The Herding Behavior, Social Media, and FOMO to Investment Decision Crypto in Gen Z - Riyan Hidayat; Mustaruddin Mustaruddin; Mochammad Ridwan Ristyawan; Giriati Giriati; Uray Ndaru Mustika (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The rapid increase in cryptocurrency adoption among Generation Z in Indonesia has raised concerns regarding investment decision-making in highly volatile digital asset markets. This study examines the influence of herding behavior, social media exposure, and fear of missing out (FOMO) on cryptocurrency investment decisions, with financial literacy as a moderating variable. A quantitative approach was employed using survey data from 200 Generation Z cryptocurrency investors in Pontianak City. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results show that herding behavior and social media significantly influence investment decisions. Fear of missing out also affects investor decision-making. Financial literacy moderates the relationship between herding behavior and investment decisions as well as between social media and investment decisions, but does not moderate the relationship between FOMO and investment decisions. These findings indicate that cryptocurrency investment decisions among Generation Z are influenced by social interactions and emotional biases.